Building an information security awareness program : defending against social engineering and technical threats - Gardner, Bill (Bill G.) (Syngress, 2014)
The best defense against the increasing threat of social engineering attacks is Security Awareness Training to warn your organization''s staff of the risk and educate them on how to protect your organization''s data. Social engineering is not a new tactic, but Building an Security Awareness Program is the first book that shows you how to build a successful security awareness training program from the ground up. Building an Security Awareness Program provides you with a sound technical basis for developing a new training program. The book also tells you the best ways to.